2014
DOI: 10.1101/gad.238782.114
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs are spatially correlated with transcription factors and regulate lung development

Abstract: Long noncoding RNAs (lncRNAs) are thought to play important roles in regulating gene transcription, but few have well-defined expression patterns or known biological functions during mammalian development. Using a conservative pipeline to identify lncRNAs that have important biological functions, we identified 363 lncRNAs in the lung and foregut endoderm. Importantly, we show that these lncRNAs are spatially correlated with transcription factors across the genome. In-depth expression analyses of lncRNAs with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 80 publications
(101 reference statements)
6
128
0
1
Order By: Relevance
“…Also in this top 10 list were genes (BMP3, CRH, and SPOCK3) previously described in lung development ( Figure 4E, with validation by RT-qPCR in S4B) (28)(29)(30)(31)(32)(33)(34). The finding that SFTA3 (aka NKX2-1-associated noncoding intergenic RNA [NANCI]) is the top differentially expressed transcript in the genome distinguishing day 15 NKX2-1 GFP+ cells is in keeping with recent reports that in developing mouse lungs this transcript is coexpressed with Nkx2-1 and shares the same regional and temporal expression pattern (35). To the best of our knowledge, 4 genes in this list (PALMD, FAM189A2, GRM8, and WDR49) have not been previously identified in the lung epithelium.…”
Section: Tp63supporting
confidence: 88%
See 1 more Smart Citation
“…Also in this top 10 list were genes (BMP3, CRH, and SPOCK3) previously described in lung development ( Figure 4E, with validation by RT-qPCR in S4B) (28)(29)(30)(31)(32)(33)(34). The finding that SFTA3 (aka NKX2-1-associated noncoding intergenic RNA [NANCI]) is the top differentially expressed transcript in the genome distinguishing day 15 NKX2-1 GFP+ cells is in keeping with recent reports that in developing mouse lungs this transcript is coexpressed with Nkx2-1 and shares the same regional and temporal expression pattern (35). To the best of our knowledge, 4 genes in this list (PALMD, FAM189A2, GRM8, and WDR49) have not been previously identified in the lung epithelium.…”
Section: Tp63supporting
confidence: 88%
“…Endodermal markers, such as GATA4, GATA6, SOX17, NODAL, and FOXA2 were upregulated early during endodermal differentiation, with retained expression of GATA6 and FOXA2 in day 15 and day 28 NKX2-1 GFP+ cells. In contrast, the transcripts NKX2-1, SFTA3, SOX9, and FOXP family members were low or absent prior to day 6, and their clear emergence in the day 15 GFP + population is consistent with their published expression during the early lung progenitor period in mouse lung development (35,36). These findings, together with the lack of mature lung marker gene expression in day 15 GFP + cells (low SCGB1A1, SCGB3A2, TP63, SFTPB, and SFTPC), further suggest the day 15 GFP + population represents a relatively undifferentiated or primordial lung progenitor population, as has been observed in early NKX2-1 + progenitors in developing mouse cells in vivo (28).…”
Section: Tp63supporting
confidence: 56%
“…Daniel Swarr and Michael Herriges (both University of Pennsylvania, Philadelphia, USA) showed that the lncRNAs Falcor and Nanci are associated with the Foxa2 and Nkx2.1 loci, respectively; they control their expression levels, and thereby early endoderm and lung development (Herriges et al, 2014). Indeed, roles for lncRNAs in controlling cell fate were an emerging theme of the meeting, also addressed by Kaveh Daneshvar (Harvard Medical School, Boston, MA, USA) looking at early endoderm differentiation.…”
Section: Expansion and Differentiation Of Endoderm Organsmentioning
confidence: 99%
“…Transgenic mice engineered to constitutively overexpress an antisense RNA targeted to Sfta3 (also known as Nanci) have abnormal epithelial morphogenesis in their developing lungs (74). A more localized, tissue-specific interference of lncRNAs using RNAi can also have phenotypic consequences.…”
Section: Animal Models and Lncrna Functionmentioning
confidence: 99%